Consistency of limb preference across unimanual feeding, bipedal locomotion, and social grooming in golden snub-nosed monkeys (Rhinopithecus roxellana). Issue 1 (2nd January 2023) - Fu, Weiwei; Xu, Jianghui; Wang, Xiaowei; Li, Yongbo; He, Shujun; Wang, Chengliang; Ren, Yi; Yang, Bin; Wu, Tong; Wang, Yan; Li, Baoguo
ABSTRACT: The golden snub-nosed monkey ( Rhinopithecus roxellana ) is a typical arboreal group-living Old World primate. While limb preference has been extensively studied in this species, limb preference consistency has not yet been explored. Here, based on 26 R. roxellana adults, we investigated whether individuals exhibit consistent motor biases in manual- (e.g., unimanual feeding and social grooming) and foot-related (e.g., bipedal locomotion) tasks and whether limb preference consistency is influenced by increased social interactions during social grooming. Results showed no consistency in the direction or strength of limb preference among tasks, except for lateral strength in handedness for unimanual feeding and footedness in the initiation of locomotion. Population-level foot preference was only found among right-handers. Marked lateral bias was found in unimanual feeding, indicating that it may be a sensitive behavioural measure for assessing manual preference, especially for provisioned populations. This study not only improves our understanding of the relationship between hand and foot preference in R. roxellana but also reveals potential differential hemispheric regulation of limb preference and the influence of increased social interaction on handedness consistency.